(3QMdI aj GdefWGQs (3acQI hcJGHI aQjb HOGjI ddEYdGe ; QShe CejQ eLOj, ajfGjGc chQfj ; JObjb dZhj heQGLYI fGUQ THGfI ; JUeje jSQ GdYHGjLjs - (3aQjb HOGjI ddEYdGes; (3GdYHGjLj, jSQs; (3THGfI, fGUQs; (3chQfj, ajfGjGcs; (3eLOj, CejQs ((3CHh XHjs (3GdeJMOI ddfTQ hGdWHGYIs, 2018)
(3aLCI ONd GdefWGO aj ONGf cKja, hHOC ajdhf jSYd hjJSGAd Yf eUOQ GdONGf GdPj ZWi GdSeGA(B."(3eG gPg GdQGFMI GdZQHjI jG eGeG ?(B"s
(3GdbUU GdYQHjIs
(3ddCWaGd ef Sf (B7 (3Edi (B10 (3SfhGJs
Keywords: (3GdbUU GdYQHjIs